Using Social Sciences in Hadith Research - Mudaris, Hudan (Universitas Cokroaminoto Yogyakarta, 2023)
Hadith research that has developed in the current period has experienced many methodological problems. This problem must be resolved immediately through dialogue with the social sciences that have developed rapidly today. Through a literature review of hadith research, it can be seen that the absence of change in religious studies is the cause of the emergence of various thoughts that are repetitive to the point of being stagnant in the gap between the study process in other fields of science. For this reason, the strategy of integrating hadith science and the absorption of social sciences has had a humanization impact along with awareness of the importance of understanding hadith as a source of basic knowledge alongside human scientific reason.